Unleashing the Potential of Kelurahan Tanjung Harapan Through the Development of a Website Profile - Raka Ramadhani Aulia Prasetyo; A Asni B; Nasuha; Wima Putri; Iqbal Rizky Ghazaly; Ahadi Noor Ahmadi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
In today's digital age, a profile website has become an essential tool for promoting the potential of a region. The rise of digital technologies and the increasing importance of the online world have made it easier to communicate and access information. This paper explores the effectiveness of a profile website in promoting the potential of a region, with a case study of the Tanjung Harapan neighborhood. Numerous studies have shown that a profile website can significantly increase public knowledge about the potential of a region and boost tourist interest in visiting the area. In the context of a neighborhood, a profile website can play a vital role in promoting its potential, including its tourist attractions, cuisine, culture, and more. By showcasing the best of what the neighborhood has to offer, a profile website can attract more visitors, thus increasing the area's economic potential. This paper highlights the importance of creating a profile website for the Tanjung Harapan neighborhood in the current digital era. The website can act as a digital brochure, presenting the best of the neighborhood, and giving visitors a taste of what they can expect to see and experience in Tanjung Harapan. The website also increases public trust and opens up opportunities to reach out to a wider audience. The findings of this paper have implications for policymakers and community leaders who seek to promote the potential of their region through digital media.